Enhancing History Education with AI-Based LMS: Supporting the Independent Curriculum in High Schools - Syarifuddin Syarifuddin; Sani Safitri; Umi Chotimah; Suratmi Suratmi; Rani Oktapiani; Dea Lestari (STAI Hubbulwathan Duri, 2025)
The integration of Artificial Intelligence (AI) in education offers new opportunities for enhancing learning engagement and effectiveness. This study aims to develop an AI-based Learning Management System (LMS) content to support the implementation of the Independent Curriculum in high schools. The research follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to create learning videos, infographics, podcasts, and digital books using AI applications such as Leonardo.ai, CapCut, Zepeto, and Canva. Expert validation and implementation trials were conducted to assess the effectiveness and usability of the developed LMS content. Validation results confirm that the AI-based LMS content enhances interactivity and engagement in learning. Implementation trials, conducted through pre-test and post-test sessions with two grade ten classes at SMA Negeri 1 Indralaya, show a 4.82% improvement in students’ learning outcomes. Observations indicate that students adapt well to AI-based learning content and that the LMS platform supports both individual and small group learning effectively. The incorporation of AI in learning media development increases student motivation and the overall effectiveness of the learning process. The AI-based LMS content provides a modern and relevant educational experience, aligning with the demands of digital-era learning. This study confirms that AI-based LMS content effectively supports the implementation of the Independent Curriculum in high schools, leading to improved student learning outcomes. The integration of AI in education presents innovative solutions to conventional learning challenges, enhancing the quality of education in the digital era.